At the speed of light - Venkataraman, G. (Hyderabad Universities Press (India), 1993)
This book is about the Theory of Relativity. The story of Relativity is, in a sense, the story of one man, Albert Einstein. The book deals only with the Special Theory, which you will find is not very difficult to understand.
Keywords: Speed; Kinematics; Theory of relativity